Публічне управління: еволюція концепцій і підходів у ретроспективі розвитку суспільних відносин - Доненко, Владислав Валерійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті обґрунтовані теоретико-методологічні засади науки публічного управління, що визначили його еволюцію від ідеї управління як ієрархічно організованої системи до концепції мережевої структури взаємодії державних, приватних і громадських організацій. Проаналізовано підходи до розуміння предмету науки публічного управління, її змісту і місця і серед інших соціальних наук. Доведено, що мережевий підхід є на сьогодні найбільш ефективною методологією аналізу сучасного політичного процесу. Встановлено, що під впливом інформаційних технологій змінюється сама природа держави, відбувається перерозподіл її функцій на наднаціональному і субнаціональному рівнях.

The article substantiates the theoretical and methodological foundations of public administration, which determined its evolution from the idea of management as a hierarchically organised system to the concept of a network structure of interaction between public, private and non-governmental organisations. Approaches to understanding the subject of public administration science, its content and place among other social sciences are analysed. It is proved that the network approach is currently the most effective methodology for analysing the modern political process. The author emphasises that under the influence of the information technologies, the very nature of the State as the most important political and legal institution is changing, and its functions are being redistributed at the supranational and subnational levels.
Public administration: evolution of concepts and approaches in the retrospective of social relations development
Keywords: публічне управління; органи місцевого самоврядувння; взаємодія держави і суспільства; мережевий підхід; public administration; local self-government bodies; interaction between the state and society; network approach